Financial hurricanes heading toward Caribbean offshore centres (Caribbean Council for Europe LondonGB, 2000)
Focuses first on tax and other financial initiatives likely to affect the Caribbean. Examines secondly financial and tax incentives impacting on the Caribbean on money laundering
Located in the Office of the Secretary General